2003
DOI: 10.1034/j.1399-3054.2003.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence‐associated mRNAs that may participate in signal transduction and protein trafficking

Abstract: The differential display technique was used to generate cDNA probes in order to identify mRNAs that are up‐regulated during senescence of Arabidopsis leaves. Three mRNAs were examined that had not previously been associated with senescence. The steady‐state levels of these mRNAs are detectable in small amounts in mature green leaves, but increase considerably as chlorophyll levels begin to decline. This relationship to senescence occurs under natural circumstances as well as when senescence is accelerated by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The present research also demonstrates senescence-induced expression of the genes encoding a calmodulin-regulated ion channel (At5g54250) and calciumbinding protein (At1g18210). Together with our recent observation concerning the involvement of a speci®c Ca 2 -dependent protein kinase in the regulation of leaf senescence (Guterman et al, 2003), these results suggest that Ca 2 may serve as a second messenger in the regulation of leaf senescence. Another interesting SAG represented by clone At1g68820 shows sequence homology to the animal apoptosis inhibitor (IAP) that regulates apoptosis by binding and inhibiting capsases (Lotocki and Keane, 2002).…”
Section: Regulatory Genessupporting
confidence: 78%
See 1 more Smart Citation
“…The present research also demonstrates senescence-induced expression of the genes encoding a calmodulin-regulated ion channel (At5g54250) and calciumbinding protein (At1g18210). Together with our recent observation concerning the involvement of a speci®c Ca 2 -dependent protein kinase in the regulation of leaf senescence (Guterman et al, 2003), these results suggest that Ca 2 may serve as a second messenger in the regulation of leaf senescence. Another interesting SAG represented by clone At1g68820 shows sequence homology to the animal apoptosis inhibitor (IAP) that regulates apoptosis by binding and inhibiting capsases (Lotocki and Keane, 2002).…”
Section: Regulatory Genessupporting
confidence: 78%
“…Recently, a few senescence-associated regulatory genes have been identi®ed. They are predicted to encode transcription factors (Eulgem et al, 2000;Hinderhofer and Zentgraf, 2001;Robatzek and Somssich, 2002), receptors for senescence perception (Hajouj et al, 2000;Robatzek and Somssich, 2002), and components of intracellular protein traf®cking (Guterman et al, 2003). Among the genes that are upregulated during leaf senescence are several whose transcript levels accumulate also under abiotic and biotic stresses (Binyamin et al, 2000;Hanfrey et al, 1996;John et al, 1997;Quirino et al, 1999;Weaver et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The other genes up-regulated in PI 312777 in response to barnyardgrass competition were those encoding kelch repeat-containing F-box family protein and RAD6 involved in protein degradation or repair pathway (Yamamoto et al 2004;Sun et al 2007); phosphatase 2C-like protein, PKD, GTP-binding protein, MYB, basic region leucine zipper and a putative senescence-associated protein functioning in signal transduction; and a Zn-finger, CONSTANS-type domain containing protein participating in gene regulation (Leung et al 1997;Sano and Ohashi 1995;Manning et al 2002;Guterman et al 2003;Landschulz et al 1988;Chen and Ni 2006). Therefore, the transcriptional activation of these genes in relative pathways can be an important step for PI 312777 in activating defense systems to adapt to the accompanying weed stress.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular biological studies have shown a large range of genes that are expressed in senescing leaves and known as SAGs (senescenceassociated genes; Dangel et al 2000). Some of the SAGs are genes involving in regulatory processes such as phosphorylation and protein-protein interaction (Guterman et al 2003); one example is a gene encoding a putative senescence-related receptor kinase (Hajouj and Michelis 2000). Receptor kinases are involved in cellular signal transduction and also protein trafficking.…”
Section: Discussionmentioning
confidence: 99%